2017
DOI: 10.1159/000481351
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Knowledge among Final-Year Medical Students in Norway

Abstract: Objectives: To assess the level of obesity knowledge in final-year medical students in Norway and to compare it to an expert group and first-year medical students. Methods: A 20-item questionnaire was specifically designed for this purpose (18 knowledge-based questions and 2 subjective questions looking at attitudes and self-perceived proficiency). All medical schools in Norway were included (n = 226). For comparison purposes, an expert group (n = 13) and first-year medical students (n = 96) were included. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…For comparison, Martins and Norsett‐Carr reported 47.8% (8.6 of 18) and 60.0% (10.8 of 18) overall scores for first‐year and final‐year medical students in Norway, respectively. It can be seen that the difference between their groups is in concordance with ours (2.2 points—12.2% vs 1.8 points—10.0%) 7 . Hence, one might speculate that the general progress (in crude numbers) following the medical educational programme is similar.…”
Section: First‐year Medical Students (N=70) (%) P Value Final‐year Mesupporting
confidence: 86%
See 1 more Smart Citation
“…For comparison, Martins and Norsett‐Carr reported 47.8% (8.6 of 18) and 60.0% (10.8 of 18) overall scores for first‐year and final‐year medical students in Norway, respectively. It can be seen that the difference between their groups is in concordance with ours (2.2 points—12.2% vs 1.8 points—10.0%) 7 . Hence, one might speculate that the general progress (in crude numbers) following the medical educational programme is similar.…”
Section: First‐year Medical Students (N=70) (%) P Value Final‐year Mesupporting
confidence: 86%
“…An 18‐item knowledge‐based questionnaire, constructed by Martins and Norsett‐Carr, was used to assess the level of obesity knowledge (Available from: https://www.karger.com/Article/FullText/481351). 7 Furthermore, final‐year medical students were also asked to complete two additional subjective questions aimed at investigating their attitudes and confidence in treating patients with obesity 7 . Data were analysed using Microsoft Excel (Microsoft Office) and MedCalc v12.1.3 (MedCalc Software bvba, Ostend, Belgium).…”
Section: First‐year Medical Students (N=70) (%) P Value Final‐year Mementioning
confidence: 99%
“…One of the challenges for effective obesity counselling is that medical residents and students do not receive sufficient training on the complex biopsychosocial etiology of obesity and evidence-based management strategies, and these topics are not well covered in medical exams [18][19][20][21][22]. A recent review concluded that across the world there is a paucity of obesity education programs for learners in health professions [23].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has become a challenge in medical care worldwide. 1 Obesity is perhaps the most prevalent form of malnutrition, prevalent in both developed and developing countries. 2 Worldwide obesity has nearly tripled since 1975.…”
Section: Introductionmentioning
confidence: 99%